CD4+ T Cell Profile and Activation Response in Sickle Cell Disease Patients with Osteonecrosis - Paula B. Daltro; Tiago O. Ribeiro; Gildásio C. Daltro; Roberto J. Meyer; Vitor Fortuna (Mediators of Inflammation)
Recent evidence suggests that abnormalities involving CD4+T lymphocytes are associated with the pathophysiology of osteonecrosis (ON); however, few studies have addressed the CD4+T cells in ON related to sickle cell disease (SCD/ON). In addition, T cells producing multiple cytokines simultaneously are often present in the inflammatory milieu and may be implicated in the immune response observed in SCD/ON. In the present study, we aimed to characterize the functional status of CD4+T cells in SCD by simultaneously determining the frequency of IFN-γ+, IL-4+, and IL-17+ CD4+T in cell cultures under exogenous stimuli. Peripheral blood mononuclear cells (PB-MNCs) from 9 steady-state SCD patients, 15 SCD/ON patients, and 19 healthy controls had functional status of CD4+T cells analyzed. Bone marrow mononuclear cells (BM-MNCs) from 24 SCD/ON patients (SCD BM) and 18 patients with ON not related to SCD (non-SCD BM) were also analyzed. We found that PB-MNC of SCD patients with or without ON presented significantly reduced TCD4+, TCD8+, and TCD4+ naïve cell frequencies and increased frequency of circulating CD4+T cells able to simultaneously produce IFN-γ+/IL4+ and IL-17+/IL4+ compared to healthy controls. Conversely, the polyclonal stimulation of BM-MNC induced an increased frequency of CD4+IFN-γ+ and CD4+IL-17+ in SCD BM compared to non-SCD BM. The increased proportion of CD4+ T cells able to produce a broad spectrum of proinflammatory cytokines after a strong stimulus indicates that the immune system in SCD/ON patients presents an expressive pool of partially differentiated cells ready to take on effector function. It is possible that this increased subpopulation may extend to inflammatory sites of target organs and may contribute to the maintenance of inflammation and the pathophysiology of osteonecrosis in sickle cell disease.